Utilization of Interactive Multimedia in Sepak Takraw Extracurricular Activities in Junior High Schools - I Putu Adi Mahardika; I Ketut Semarayasa; Luh Putu Tuti Ariani (Jurnal Media dan Teknologi Pendidikan, 2025)
This study aims to develop and validate interactive multimedia-based learning media for sepak takraw using Adobe Animate to support extracurricular activities in junior high schools. The study arises from the limited use of conventional media in explaining sepak takraw techniques, which affects students’ understanding and skills. The research employed the Research and Development (R&D) method with the 4D model, consisting of define, design, develop, and disseminate stages. Data were collected through interviews, surveys, questionnaires, and literature studies, and analyzed using descriptive quantitative techniques. The resulting product is an interactive multimedia application accessible via desktop and Android devices. Validation results showed that the material expert gave an average score of 4.7 and the media expert 4.67, both categorized as very good. These findings indicate that the developed media is feasible for improving students’ sepak takraw skills, learning motivation, and independent learning. The implication of this study suggests that Adobe Animate–based interactive multimedia can serve as an innovative alternative for coaches to create more engaging, adaptive, and student-centered learning experiences in the digital era.